DEVELOPMENT OF A NATURAL PH INDICATOR BASED ON ANTHOCYANIN-CONTAINING LOCAL RAW MATERIALS AND VISUAL ASSESSMENT OF FOOD PRODUCT FRESHNESS - S.N.Obloberdiyev; G.Sh.Korabekova; F.Sh.G‘ulomova; M.J.Bekmurodova; Sh.E.Ulashova; Z.A.Madusmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This study focuses on the development of a natural pH indicator based on anthocyanin-containing local raw materials for the visual assessment of food product freshness. Anthocyanins are natural pigments that change color depending on the acidity of the medium. The prepared indicator was used to monitor pH changes in food products during storage. The results showed that the natural indicator can visually reflect freshness loss through clear color changes. This approach is eco-friendly, simple, and suitable for preliminary quality control of food products.